Analisis Sosiologi Sastra Cerpen Penthouse 2601 Karya Djenar Maesa Ayu dan Implikasi Pembelajaran Bahasa Indonesia - Resvya Noer Fauzy; Diena San Fauziya (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Short stories are part of a literary genre that describes the environment. One of the important things in short stories is how the author's events and thoughts can be expressed well so that they can be understood and enjoyed well by readers. To find information contained in short stories in more depth, research can be done in the form of analysis. The aim of this research is to examine the content of the short story entitled